2020
DOI: 10.1093/jn/nxaa037
|View full text |Cite
|
Sign up to set email alerts
|

Daily Preventive Zinc Supplementation Decreases Lymphocyte and Eosinophil Concentrations in Rural Laotian Children from Communities with a High Prevalence of Zinc Deficiency: Results of a Randomized Controlled Trial

Abstract: Background Zinc deficiency impairs immune function and is common among children in South-East Asia. Objectives The effect of zinc supplementation on immune function in young Laotian children was investigated. Methods Children (n = 512) aged 6–23 mo received daily preventive zinc tablets (PZ; 7 mg Zn/d), daily multiple micronutrient powder (MNP; 10 mg Zn/d, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Cellular zinc levels are highly buffered, and hence zinc depletion and restitution at a clinical level in this cohort may not have substantially altered intracellular zinc metabolism and function for cells involved in immune responses [ 27 ]. Our results are in line with a trial of preventive zinc supplementation in Laotian children, which likewise did not detect an effect from zinc on T cell cytokines, LPS-stimulated cytokines and T cell concentrations [ 28 ]. Previous data from in vitro treatment of cell lines with high or low zinc concentrations, from experimental animal models with markedly zinc-depleted or loaded diets or from humans receiving experimentally controlled zinc depletion diets may not apply to this more complex population of children with a variety of dietary and infectious exposures.…”
Section: Discussionsupporting
confidence: 91%
“…Cellular zinc levels are highly buffered, and hence zinc depletion and restitution at a clinical level in this cohort may not have substantially altered intracellular zinc metabolism and function for cells involved in immune responses [ 27 ]. Our results are in line with a trial of preventive zinc supplementation in Laotian children, which likewise did not detect an effect from zinc on T cell cytokines, LPS-stimulated cytokines and T cell concentrations [ 28 ]. Previous data from in vitro treatment of cell lines with high or low zinc concentrations, from experimental animal models with markedly zinc-depleted or loaded diets or from humans receiving experimentally controlled zinc depletion diets may not apply to this more complex population of children with a variety of dietary and infectious exposures.…”
Section: Discussionsupporting
confidence: 91%
“…The main trial was designed to compare two forms of daily preventive zinc supplementation (7-mg/d zinc as zinc sulfate, provided as a dispersible tablet or 10-mg/d zinc as zinc gluconate, provided in a multiple micronutrient powder) versus therapeutic zinc supplementation (20-mg/d zinc as zinc sulfate, provided for 10 days in relation to an episode of diarrhea) or placebo on young children's physical growth and risk of infection over the 36-week intervention period. Detailed descriptions of the overall study design, as well as the effect of the interventions on the primary outcomes (i.e., physical growth, diarrhea incidence, hemoglobin and micronutrient status, and innate and adaptive immune response) have been reported previously [11][12][13][14]. The current analyses address secondary outcomes of the trial.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…In addition, although the impact of picky eating on the growth and weight status of children is still controversial [ 22 , 23 , 54 , 62 ], this study found that children with picky eating behaviors had lower zinc levels and were significantly associated with a high prevalence of zinc deficiency. In addition to improving immunity [ 63 , 64 ] and reducing the duration and severity of diarrhea in children [ 65 , 66 ], recent clinical trials have shown that zinc supplementation can improve children’s development and physical activity. A randomized clinical trial of 251 infants by Colombo et al showed that zinc supplementation has a positive effect on of sensorimotor development [ 67 ].…”
Section: Discussionmentioning
confidence: 99%